Miocene detachment faulting predating EPR propagation: Southern Baja California. Issue 5 (20th May 2016) - Bot, Anna; Geoffroy, Laurent; Authemayou, Christine; Bellon, Hervé; Graindorge, David; Pik, Raphaël
Abstract: At the southern tip of the Baja California peninsula, we characterize the onshore structures and kinematics associated with crustal necking leading up to the Pliocene breakup and early East Pacific Rise seafloor spreading. From a combination of tectonic field investigations, K‐Ar and cosmogenic isotope dating and geomorphology, we propose that the Los Cabos block represents the exhumed footwall of a major detachment fault. This north trending detachment fault is marked by a conspicuous low‐dipping brittle‐ductile shear zone showing a finite displacement with top to the SE ending to the ESE. This major feature is associated with fluid circulations which led to rejuvenation of the deformed Cretaceous magmatic rocks at a maximum of 17.5 Ma. The detachment footwall displays kilometer‐scale corrugations controlling the present‐day drainage pattern. This major detachment is synchronous with the development of the San José del Cabo Basin where syntectonic sedimentation took place from the middle Miocene to probably the early Pliocene. We propose that this seaward dipping detachment fault accommodates the proximal crustal necking of the Baja California passive margin, which predates the onset of formation of the East Pacific Rise spreading axis in the Cabo‐Puerto Vallarta segment. Our data illustrate an apparent anticlockwise rotation of the stretching direction in Baja California Sur from ~17 Ma to the Pliocene. Key Points: An unrecognized detachment fault allowed the opening of the San Jose del Cabo Basin The detachment fault accommodated the crustal necking with a N118E trending sigma3 The detachment fault activity occurred from approximately 13 to 5 Ma, predating the EPR propagation